2020
DOI: 10.1002/cncr.32905
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of PALB2 germline mutations and characteristics of PALB2‐related breast cancer: Screening of 16,501 unselected patients with breast cancer and 5890 controls by next‐generation sequencing

Abstract: Background Partner and localizer BRCA2 ( PALB2 ) is a breast cancer predisposition gene, but the clinical relevance of PALB2 germline mutations in Chinese patients with breast cancer remains unknown. This study attempted to investigate the full prevalence and spectrum of PALB2 germline mutations in China and the associations between PALB2 germline mutations and breast cancer risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 25 publications
6
28
4
1
Order By: Relevance
“…Our study revealed that PALB2 pathogenic variants are detected in approximately 1% of Russian high‐risk BC patients, while their frequency in consecutive BC patients is approximately 1.5 times lower. These estimates are similar to the data obtained in North American, European and Asian studies 11‐15 . We also identified five OC patients carrying PALB2 pathogenic alleles; however, despite analyzing more than 1800 women with OC, our data on PALB2 contribution in OC risk are not conclusive.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our study revealed that PALB2 pathogenic variants are detected in approximately 1% of Russian high‐risk BC patients, while their frequency in consecutive BC patients is approximately 1.5 times lower. These estimates are similar to the data obtained in North American, European and Asian studies 11‐15 . We also identified five OC patients carrying PALB2 pathogenic alleles; however, despite analyzing more than 1800 women with OC, our data on PALB2 contribution in OC risk are not conclusive.…”
Section: Discussionsupporting
confidence: 86%
“…European and Asian studies. [11][12][13][14][15] We also identified five OC patients carrying PALB2 pathogenic alleles; however, despite analyzing more These PALB2 pathogenic variants were described in our previous reports. 22,23 b These PALB2 mutation carriers were identified by whole exome sequencing within another study.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations